Antimicrobial Properties Related to Anti-Acne and Deodorant Efficacy of Hedychium coronarium J. Koenig Extracts from Pulsed Electric Field Extraction - Manasanan Mitchaleaw; Saranya Juntrapirom; Anurak Bunrod; Watchara Kanjanakawinkul; Artit Yawootti; Wannaree Charoensup; Sasithorn Sirilun; Wantida Chaiyana (MDPI AG, 2024)
This study investigated the potential of pulsed electric field (PEF) extraction in enhancing the antimicrobial properties related to anti-acne and deodorant properties of Hedychium coronarium extract. The dried leaf and rhizome of H. coronarium were extracted using 95% v/v ethanol through both conventional solvent extraction and PEF extraction techniques (10, 14, and 20 kV/cm). The chemical composition of the extracts was analyzed. The antimicrobial activities, specifically in relation to acne treatment against Cutibacterium acnes and deodorant properties against Staphylococcus aureus, Bacillus subtilis, Micrococcus luteus, Pseudomonas aeruginosa, and Escherichia coli, were determined. The irritation profile of was evaluated using the hen's egg chorioallantoic membrane test. The results showed that PEF extraction increased the extract yield, particularly at an electric field strength of 20 kV/cm. Furthermore, PEF extraction significantly enhanced the ellagic acid content, particularly in the leaf extract. Furthermore, the leaf extract demonstrated stronger inhibitory effects against microorganisms associated with body odor and acne compared to the rhizome extract. Notably, all extracts exhibited no signs of irritation, indicating their safety. Overall, the findings suggest that PEF extraction from H. coronarium enhances yield, bioactive compound content, and antimicrobial effects. This indicates the potential of the extract for acne treatment and deodorant use.